Crinipellis siamensis (Marasmiaceae, Agaricales), a new macrofungus from northern Thailand - Kumla, Jaturong; Phonrob, Wiphawanee; Lumyong, Saisamorn; Suwannarach, Nakarin (Phytotaxa, 2024)
A new Crinipellis species, described herein as C. siamensis, was collected from northern Thailand during the rainy seasons in 2022 and 2023. This species was identified based on morphological characteristics and molecular data. Crinipellis siamensis is characterized by its crinipelloid basidiomata, grayish orange to brown pileus, elongated to cylindrical basidiospores, and hair-like terminal cells on the pileus surface. Phylogenetic analysis of combined internal transcribed spacer (ITS) and the large subunit (nrLSU) of nuclear ribosomal DNA (rDNA) regions revealed that C. siamensis is well-supported as a distinct monophyletic member within the genus Crinipellis. A full description, color photographs, illustrations, and a phylogenetic tree showing the position of C. siamensis are provided. Morphologically similar and related species to the new species are also discussed.